Problematika Pinjaman Online (Pinjol) Berbasis Syariah dalam Perspektif Ekonomi Syari’ah - Fadly Raman; Sayyidina Taqwa; Ahmad Abroza; Afton Zuhri Adnan (Jurnal Multidisiplin Indonesia, 2026)
This study analyzes the problems of Sharia-compliant online loans (pinjol) from a sharia economic perspective using a qualitative, descriptive approach and a literature review method. The main findings reveal three crucial issues: the regulatory dualism between the Financial Services Authority (OJK) Regulation (POJK) and the fatwa of the National Council of Indonesian Ulema Council (DSN-MUI), the deviation of digital financing contracts, such as murabahah, into hidden fees resembling usury (riba), and the negative impact on the maqasid (objectives) of sharia, specifically hifz al-mal (the principle of right to freedom from evil) and hifz al-nafs (the principle of right to freedom from evil). Although loan disbursement is expected to reach IDR 1.85 trillion by 2025, operational practices often violate the principles of al-ghunmu bi al-ghurmi (the principle of right to freedom from evil) and transparency due to low literacy and weak oversight. The study recommends Sharia-specific regulatory reforms, regular contract audits, and increased literacy to align Sharia fintech with Islamic economic goals. These findings contribute to strengthening Indonesia’s position as a global hub for the halal economy.